A Novel, Low-Cost Glaucoma Calculator to Identify Glaucoma Patients and Stratify Management. (31st July 2022) - Laroche, Daniel; Rickford, Kara; Mike, Elise V.; Hunter, Liane; Ede, Ezekiel; Ng, Chester; Douglas, John
Abstract : Glaucoma is a leading cause of preventable blindness globally. Nearly, half of the patients who have glaucoma in the United States are unaware of their diagnosis, and this number is far greater in resource poor areas. The risk of progressive and irreversible loss of vision is decreased with an early diagnosis, and better access to treatment is vital to improve the visual outcome for patients. We therefore postulated that a minimally invasive, low-cost calculator used to predict the risk of glaucoma and inform the course of follow-up care will improve patient prognosis. We retrospectively examined data from 104 eyes of patients who underwent a complete ocular examination, visual field, and corneal pachymetry at Advanced Eye Care of New York (54 with glaucoma and 50 controls). Receiver operating curves (ROC) were utilized to determine the correct glaucoma classification rates of the Laroche glaucoma calculator (Range −3 to 18), a novel tool that combines age, intraocular pressure (IOP), and central corneal thickness (CCT) into a composite metric. Additionally, we compared the discriminatory power of this calculator to age, intraocular pressure (IOP), and central corneal thickness (CCT) separately. A score of greater than or equal to 6 on the Laroche glaucoma calculator (sensitivity 90.74%, specificity 64.00%, correct classification 77.88%) optimizes the accuracy of this tool. Compared to IOP (Area Under the Curve (AUC) = 0.72, chi 2  = 4.21, p = 0.04 ) and CCT (AUC = 0.53), chi 2 24.72 p < 0.001 ), the Laroche glaucoma calculator (AUC = 0.81) was significantly better at discriminating against glaucoma patients vs. controls. These results demonstrate that the Laroche calculator is a novel, effective tool for identifying glaucoma, and it may provide a low-cost risk stratification tool, particularly in areas with limited resources.